PEMBELAJARAN LITERASI FINANSIAL DALAM PERKEMBANGAN SOSIOEMOSIONAL ANAK USIA DINI MELALUI KEGIATAN MENABUNG DI RA NURUL YUSRO - Henny Noverita; Sharina Munggaraning Westhisi (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2021)
Saving activities from an early age are a form of financial literacy learning so that it is an important part to be applied for students aged 4-6 years to build a habit of setting aside some of their pocket money. The purpose of this study is to recognize good financial literacy education in early childhood schools. Education on financial literacy is one of which is a savings program and has become an education program at RA Nurul Yusro. This method uses descriptive qualitative research in the form of data collection techniques such as interviews, observation, and documentation. The technique used is thematic analysis techniques. The subjects in this study were group B children and two class teachers. Based on the results of thematic data analysis and discussion, it can be concluded that children's socioemotional abilities can be improved through saving activities. The result of this research is the implementation of saving activities as a form of financial literacy learning in developing early childhood socio-emotional development. The implementation of learning-saving activities will involve students so that during the learning process there will be a development of a sense of responsibility, sharing, and discipline from early childhood.Kegiatan menabung sejak dinimerupakan salah satu kegiatan  pembelajaran literasi keuangan sehingga menjadi bagian yang  penting untuk diterapkan bagi siswa usia 4-6 tahun untuk membangun kebiasaan menyisihkan sebagian uang sakunya.Tujuan penelitian ini adalah mengenal Pendidikan  literasi  keuangan,baikdi  sekolah anak usia dini.Pendidikantentangliterasikeuangansalah satunya adalah  program menabung dan sudah menjadi program penyelenggaraan pendidikan di RA Nurul Yusro.Metode ini menggunakan  penelitian deskriptif kualitatif berupa Teknik pengumpulan data seperti wawancara, observasi, dan dokumentasi.Adapun teknik yang digunakan adalah teknik analisis tematik. Subjek dalam penelitian ini anak  kelompok B dan dua Guru kelas. Berdasarkan hasil analisis data tematikdan pembahasan maka dapat disimpulkan bahwa kemampuan sosioemosinal anak dapat ditingkatkan melalui kegiatan menabung.Hasil penelitian ini adalah implementasi kegiatan menabung sebagai bentuk pembelajaran literasi finansial dalam mengembangkan sosioemosional anak usia dini. Pelaksanaan pembelajaran kegiatan menabung  akan melibatkan peserta didik, sehingga pada saat proses pembelajaran akan terlihat perkembangan rasa tanggung jawab, berbagi dan kedisplinan dari anak usia dini.